Relationship between proximal to distal phalangeal articular angle and Hallux Pronation in Hallux Valgus deformity - Yun Jae Kim; Ho-Seong Lee; Young Rak Choi (Scientific Reports)
Abstract This study aimed to determine whether hallux pronation influences the proximal to distal phalangeal articular angle (PDPAA) and evaluate its relationship with postoperative recurrence. We included 94 hallux valgus (HV) patients who underwent distal chevron metatarsal osteotomy (DCMO) alone (DCMO-only group, n = 15) and DCMO with Akin osteotomy (DCMO + Akin group, n = 79). Preoperative additional toe radiographs were taken under supination stress to position the pronated toe as a true anteroposterior orientation. The mean follow-up period was 12.9 months. The PDPAA on weightbearing radiograph did not significantly differ from the PDPAA corrected by supination stress (5.0 ± 7.0 vs. 4.7 ± 6.4 degrees, p = 0.820). The DCMO-only group showed a higher recurrence rate than the DCMO + Akin group (33.3 vs. 7.6%, p = 0.014). In the DCMO-only group, those with recurrence had significantly higher preoperative PDPAA values than those without recurrence (7.6 ± 5.9 vs. -0.2 ± 3.0 degrees; respectively, p = 0.013). In conclusion, the PDPAA was not significantly influenced by the hallux pronation in patients with HV. For HV patients with a large preoperative PDPAA, additional Akin osteotomy should be considered to prevent recurrence.